STANDING UP TO AGEISM: PERCEPTIONS OF SIXTY AND EIGHTY YEAR-OLD ADULTS WHO REJECT BENEVOLENT AGEISM. (20th December 2022) - Chasteen, Alison; Saleem, Zainab; Horhota, Michelle
Abstract: Older people encounter ageism in a variety of daily contexts, yet the consequences of confronting ageist behavior by older targets are not well understood. The present study asked whether the age of the older target who accepts versus rejects an act of benevolent ageism results in different impressions of the older target. Young (N = 368) and older (N = 388) adults read a scenario in which either a 60 or 80 year-old individual accepted or rejected benevolent ageism in the form of unwanted help. Participants then evaluated the older target's warmth, competence, and overall impression of the target. Consistent with pre-registered hypotheses, competence ratings increased but warmth and overall impression ratings decreased when the older target rejected benevolent ageism compared with accepting it. Also consistent with predictions, older participants rated the older target more positively on all measures compared with younger participants. Surprisingly, the 80 year-old target was rated as warmer and made a more positive overall impression than did the 60 year-old target. Target age did not moderate reactions to accepting or rejecting unwanted help, suggesting that perceivers did not distinguish between young-old and old-old targets when evaluating an older target that confronts benevolent ageism. Taken together, these findings are consistent with research on confronting prejudice in general, whereby such confrontations can result in both positive and negative outcomes. Although older adults may reaffirm their competence through rejecting benevolent ageism they will also face the social cost of being viewed as less warm.